STRATEGI PEMASARAN JASA PADA HOTEL ROSALI SITUBONDO - Fizaldi, Bayu; Ihsan, Anas Malik Fauzan; Ibad, Ersatul; Pratama, Rico Arif; Aziz, Muhamad Zitkul (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
The hotel industry is a service industry that offers room service, food and beverage providers and other services to the general public which are managed commercially. The research entitled "Service Marketing Strategy at the Rosali Hotel Situbondo" aims to analyze the marketing strategy carried out by the Rosali Hotel Situbondo. The service marketing strategy analysis used in this research is the marketing mix or 7P which consists of Product, Price, Place, Promotion, People, Physical Evidence, Process. The type of research used is qualitative research with descriptive methods where the data used is secondary data, namely literature studies. The results of this research show that the product is a room with various types and facilities. In Price, prices are determined based on the facilities that consumers will get. For promotion, use advertising promotions, personal sales, public relations and sales promotions. For location, Hotel Rosali is in a strategic location. Next process, Hotel Rosali starts with the marketing role and all marketing results processes reported by the marketing manager. And the last one is physical evidence, Hotel Rosali has a sturdy and distinctive building.